A PRELIMINARY SURVEY OF TREE SPECIES DIVERSITY: A CASE STUDY OF FEDERAL UNIVERSITY WUKARI - Anongo, M'ember Catherine; Yerima, Mercy joseph (FUDMA JOURNAL OF SCIENCES, 2023)
The impact of anthropogenic activities on tree species diversity of a selected sub-sample of the Federal University Wukari Campus comprising of four sampling Sites (A, B, C and D) was investigated using the Shannon-Wiener, Margalefs and Menhinik diversity indices. Tree felling is the commonest human activity. The infrastructural developments and anthropogenic activities among the four sampling sites ranges from low to high. A total of 203 individual tree species of 20 species from 15 families was encountered in the study area. The dominant families were Arecaceace, Fabaceae, Anacardiaceae, Lamiaceae and Moraceae. Elaies guineensis (80) was the most dominant tree species with the highest relative density (RD) of 39.4% at Site D while the lowest RD of 0.49 were encountered at Sites A, B and C. The most abundant tree species were Elaies guineensis and Mangifera indica due to their economic importance. About 35% of the trees were exotic while 65% were native. A high Shannon-Wiener index value of 0.78 and Margalefs index value of 14.869 were observed. Analysis of the diversity indices of the 20 species reveals the sensitivity of the Shannon-Wiener index than the Margalefs index, though the two indices shows relative diversity of tree species according to their ranges. The high population size of the indigenous trees with higher economic uses is a strong indicator of loss of tree genetic resources that play critical roles in local diversification of the ecosystems to make them more resilient for what is to come with respect to climate change regulation.